2006
DOI: 10.4103/0019-509x.29420
|View full text |Cite
|
Sign up to set email alerts
|

High-risk human papillomavirus, tumor suppressor protein p53 and mitomycin-C in invasive squamous cell carcinoma cervix

Abstract: BACKGROUND: Clinical data relating to human papillomavirus (HPV) infection and p53 status in cervical cancer has been sparse and confusing. AIM: To evaluate high-risk HPV and expression of tumor suppressor protein p53 in squamous cell carcinoma of cervix and to assess response to mitomycin-C in neo-adjuvant chemotherapy. SETTING AND DESIGN: RESULTS:All patients with cancer cervix were positive for high-risk HPV DNA having relative light units/cut off values ranging from 3.4-2389.21 (P value = 0.006). High vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
2
3
0
Order By: Relevance
“…A similar staining pattern of HPV 16/18 was observed by Menon et al [26] and Choudhury and Singh. [25] In the present study, no significant statistical association could be found between HPV infection and p53 expression (P = 0.377 for CIN and 1.00 for carcinoma cervix) which was in accordance with Jeffers et al [9] and Rajaram et al [12] On the contrary, Dellas et al [10] found a significant correlation between HPV infection and p53 immunoreactivity. We also did not find any significant statistical correlation between HPV infection and bcl2 expression.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…A similar staining pattern of HPV 16/18 was observed by Menon et al [26] and Choudhury and Singh. [25] In the present study, no significant statistical association could be found between HPV infection and p53 expression (P = 0.377 for CIN and 1.00 for carcinoma cervix) which was in accordance with Jeffers et al [9] and Rajaram et al [12] On the contrary, Dellas et al [10] found a significant correlation between HPV infection and p53 immunoreactivity. We also did not find any significant statistical correlation between HPV infection and bcl2 expression.…”
Section: Discussionsupporting
confidence: 90%
“…The results were in accordance with those found by several other authors. [12][13][14] However, many authors have found lower positivity rates ranging between 10% and 30% respectively. [15][16][17] In contrast, Grace et al [7] and few other workers [11,18,19] found much higher rates of p53 expression ranging between 69% and 100% in squamous cell carcinomas of the cervix.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SCCs are the most common histological type as the most common etiological agent responsible for cervical cancer is HPV which most commonly affects the lining cervical [19,23] epithelium. HSIL was the common histological subtype in premalignant lesions in the present study which is in concordance to the studies done by Jeffers et al [24] The mean age of presentation of malignant lesions (49.04 ± 10.42 years) is almost similar to that reported by Rajaram et al [25] (52.1 ± 12.46 years), Tan et al [26] (51.1 years), Koncar et al [27] (50 years), and Tan et al [28] (50.3 years). Furthermore, the mean age of presentation of premalignant lesions (41.00 ± 8.89 years) is younger than that of malignant lesions.…”
Section: Discussionsupporting
confidence: 82%
“…Using the conserve L gene of virus capsid (20). Since only high risk types of HPV cause cervical cancer, it is necessary to determine the HPV types in clinical samples (21). Considering the extent of HPV infection, it seems necessary to determine the most prevalent HPV types in each population in order to design an effective screening program, management, and vaccination against the prevalent virus types in the population.…”
mentioning
confidence: 99%